The Estimation of the Number of Binding Sites for Antibody on Antigen Molecules with Reference to Factor VIII and its Antibody - Pool, Judith; Biggs, Rosemary; Miller, R. G (Thrombosis and Haemostasis, 1976)
The theoretical basis for determining the number of antibody sites on antigen molecules is examined. The theoretical considerations are applied to factor VIII molecules. Examples based on data available at the Oxford Haemophilia Centre are calculated to illustrate the approach. It is concluded that there are few sites on each factor VIII molecule for human antibody. The three antibodies for which reasonable data were available suggest 1–3 sites for human antibody. The data for rabbit antibody suggest 5–6 sites per factor VIII molecule.